Shaping The Future of Medical Education in Iraq after The WFME Recognition: Responsibilities and Looking Ahead - Omar Mustafa; Ghanim Alsheikh (University of Kirkuk, College of Medicine, Kirkuk, Iraq, 2024)
The recent recognition of Iraq's National Council for Accreditation of Medical Colleges (NCAMC) by the World Federation for Medical Education (WFME) marks a crucial step towards enhancing medical education quality. However, this acknowledgment brings responsibilities. Both NCAMC and Iraqi medical colleges must embrace continuous quality improvement methodologies like the PDSA/PDCA cycles and innovate in education for sustainability. Iraqi medical colleges should view accreditation as the beginning of a comprehensive journey towards excellence, integrating total quality management principles into their operations and striving for innovation beyond basic standards. NCAMC, on the other hand, must leverage this recognition to drive substantial improvements, including establishing an online database for self-evaluation data and addressing internal challenges like funding and assessor development. Strategic collaboration between NCAMC, medical colleges, and stakeholders is vital to maximize accreditation's impact on healthcare outcomes and education effectiveness. In conclusion, WFME's recognition signifies a commitment to excellence in Iraqi medical education, necessitating collaborative efforts for continuous improvement and a brighter future in healthcare education and outcomes.